Risky Business: Reopening Recreational Sport Facilities During COVID-19 - Leeann M. Lower-Hoppe; Annemarie Farrell; Alina Cioletti; Ali Talcott; Mackenzie Rector; Shea M Brgoch; Robert J. Barcelona (Journal of Applied Sports Management, 2023)
At the onset of COVID-19, sport and fitness administrators shut down facilities to mitigate viral spread. To reopen facilities, safety protocols and policies reflecting risk mitigation strategies were established. This case study adopted the International Standards Organization’s risk management framework to explore strategies for reopening collegiate recreational sport facilities during the pandemic. Document analysis was employed to analyze the reopening plans of four collegiate recreation departments across North America. The reopening plans focused on the risk assessment and treatment process and used a phased approach, with strategies moving from risk avoidance to risk reduction and transfer. Common risk management strategies across facility areas included social distancing, reduced programming/services, and increased sanitization. However, notable differences were found based on risk unique to distinct facility areas. Implications for practice include use of a customized facility inspection checklist, adherence to new industry safety standards, and clear communication with stakeholders.
Keywords: risk management; risk assessment; risk treatment; policy formation; collegiate recreation